2008
DOI: 10.1536/ihj.49.713
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Temporary Inferior Vena Cava Filter in the Treatment of Deep Vein Thrombosis in Critically-Ill Patients

Abstract: SUMMARYWe studied the clinical courses of patients with deep vein thrombus (DVT) who underwent insertion of temporary inferior vena cava filters (tIVCF) and evaluated the effectiveness of the tIVCF.From January 2003 to March 2008, tIVCF were placed in 12 patients with a diagnosis of DVT in the Intensive Care Unit (ICU) of Gunma University Hospital. The mean age of the patients was 52 ± 16 years (range, 18-82). Eight were medical patients who had not undergone any prior surgery, and 4 were postoperative patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…To our best knowledge, there have been three reports on IVC complications using a Toray Neuhaus Protect catheter. Oshima et al . used the IVC catheter in 12 patients with DVT; there were no thrombi in the filter.…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, there have been three reports on IVC complications using a Toray Neuhaus Protect catheter. Oshima et al . used the IVC catheter in 12 patients with DVT; there were no thrombi in the filter.…”
Section: Discussionmentioning
confidence: 99%
“…For preventing PTE, temporary IVC filters are reported to be as effective as permanent filters, 5) and these retrievable IVC filters have been used effectively in patients with transient risks.…”
Section: Discussionmentioning
confidence: 99%
“…Temporary intravenous filter placement may also play a key role in the prevention of PTE in patients with medical refractory DVT. 10) On the other hand, it has been reported that the incidence of bleeding complications does not depend on thrombosis location.…”
Section: )mentioning
confidence: 99%